Analisa Penggunaan Teknologi Wireless Power Transfer - Arsanto Narendro (CV. Multi Kreasi Media, 2026)
The extensive adoption and rapid expansion of mobile gadgets have positioned wireless power transfer (WPT) as a critical domain of scientific inquiry. A compelling feature of WPT lies in its ability to offer a versatile and economical charging solution, eliminating the necessity for a direct physical link to power outlets—a particularly beneficial trait when manual connection is impractical for the user. Historically, battery replenishment for such hardware has relied on wired systems, necessitating a tethered attachment to electricity via physical cabling. In contrast, WPT facilitates the transmission of energy through the air over brief spans, utilizing either magnetic fields generated by inductive coil coupling or electric fields arising from capacitive electrode interaction, which are subsequently captured by an antenna for functional use. This paper provides a comprehensive analysis of current WPT methodologies, their functional mechanisms, practical implementations, and prospective research trajectories within this nascent field. Despite existing limitations, WPT represents a transformative advancement poised to fundamentally reshape the operational framework of mobile networks, the Internet of Things (IoT), and associated future technological ecosystems.